Characterization of nontyphoidal Salmonella strains from a tertiary hospital in China: serotype diversity, multidrug resistance, and genetic insights - Ma, Wanshan; Cui, Xiaodi; Dong, Xiutao; Li, Xinpeng; Liu, Ke; Wang, Yujiao; Shi, Xiaohong; Chen, Liang; Hao, Mingju (Frontiers in Cellular and Infection Microbiology, 2024)
Objective Nontyphoidal Salmonella is a significant public health concern due to its ability to cause foodborne illnesses worldwide. This study aims to characterize the nontyphoidal Salmonella strains isolated from patients in China. Methods A total of 19 nontyphoidal Salmonella strains were characterized through serovar identification, antimicrobial susceptibility testing (AST), biofilm formation assessment. Genetic relatedness was determined using pulsed-field gel electrophoresis (PFGE). WGS was employed to decipher the resistance mechanism and to contextualize the S. serovar Mbandaka strains among previously sequenced isolates in China. The biofilm associated mrkA gene was examined by PCR. Results The predominant serovar identified was S. Enteritidis, followed by S. Mbandaka, S. Thompson, S. Livingston, S. Alachua, and S. Infantis. PFGE analysis indicated a notable genetic similarity among the S. Mbandaka isolates. Phylogenetic analysis suggested that these strains were likely derived from a single source that had persisted in China for over five years. One multidrug resistance (MDR) S. Enteritidis isolate carried a highly transferable IncB/O/K/Z plasmid with blaCTX-M-15. One S. Thompson strain, harboring the mrkABCDF operon in an IncX1 plasmid, isolated from cutaneous lesions, demonstrated robust biofilm formation. However, no mrkABCDF loci were detected in other strains. Conclusion Our study emphasizes the importance of persisted surveillance and prompt response to Salmonella infections to protect public health. The dissemination of blaCTX-M-15-harboring IncB/O/K/Z plasmid and the spread of virulent mrkABCDF operon among Salmonella in China and other global regions warrant close monitoring.